2015
DOI: 10.7324/japs.2015.501104
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Triterpenes and Sterols from Pipturus arborescens (Link) C.B. Rob.

Abstract: The triterpenes, squalene (1), friedelin (2) and a mixture of ursolic acid (3a) and oleanolic acid (3b) in a 2:3 ratio, and a mixture of β-sitosterol (4a) and stigmasterol (4b) in a 2:1 ratio, obtained from the dichloromethane extract of Pipturus arborescens (Link) C.B. Rob., were evaluated for their anti-proliferative activities against three human cancer cell lines, breast (MCF-7) and colon (HT-29 and HCT-116), and a normal cell line, human dermal fibroblast-neonatal (HDFn) using the in vitro PrestoBlue ® ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This implies that HCT-116 cells are more responsive to the treatments used. Differences in treatment response between colon cancer cell lines were also observed in previous studies [44][45][46]. It was reported that variations in the expression profiles of genes associated with drug sensitivity in HCT-116 and HT-29 cells could be an important factor dictating how the cells respond to inhibitory compounds [47].…”
Section: Resultsmentioning
confidence: 52%
“…This implies that HCT-116 cells are more responsive to the treatments used. Differences in treatment response between colon cancer cell lines were also observed in previous studies [44][45][46]. It was reported that variations in the expression profiles of genes associated with drug sensitivity in HCT-116 and HT-29 cells could be an important factor dictating how the cells respond to inhibitory compounds [47].…”
Section: Resultsmentioning
confidence: 52%
“…A difference in treatment responses between two colon cancer cell lines was also seen in previous studies. 16,17 It was reported that changes in the expression profiles of genes associated with drug sensitivity between HCT-116 and HT-29 could influence how the cells react to different inhibitory compounds. 18 A similar study using four human colon cancer cell lines (HCT-116, HT-29, HCT-15, and KM-12) showed that gene expression profiling after inhibition of signal transduction by 17-allylamino-17-demethoxygeldanamycin, a known inhibitor of the hsp90 molecular chaperone, could explain the cells' response under different treatment parameters.…”
Section: Results and Discusionmentioning
confidence: 99%